The Judicial Considerations in Imposing Criminal Sentences on Offenders of Illegal Distribution of Subsidized Fertilizer (Study of Decision No. 191/Pid.Sus/2024/PN Mgl) - Cahyono, Riki; Seregig, I Ketut (The Future of Education Journal, 2025)
Indonesia's agricultural sector has been experiencing significant growth and serves as the backbone of the economy. However, there are major challenges in meeting the needs of society, which are often exploited by individuals for personal gain, such as the illegal distribution of subsidized fertilizer. One case tried at the Menggala District Court revealed the practice of selling subsidized fertilizer without the required sale and purchase agreement (SPJB) and violating valid distribution regulations. This research investigates how judges consider criminal sentences for offenders and the legal criteria used to classify this illegal fertilizer distribution as a criminal act. The findings indicate that the judge considered all evidence, witness testimonies, as well as grounds for exonerating criminal liability such as justifying and excuse defenses. The classification of illegal fertilizer distribution as a criminal offense refers to several legal regulations governing the distribution of subsidized fertilizers, including Emergency Law No. 7 of 1955, Government Regulation No. 8 of 1962, and Presidential Regulation No. 15 of 2011. This study recommends that the government strengthen regulations on subsidized fertilizer distribution to close legal loopholes, improve monitoring of distribution channels, and educate distributors and agents about the legal consequences of violations. Moreover, it is hoped that society will become more aware of the importance of complying with the rules and report any distribution irregularities to law enforcement to prevent illegal practices.